2008
DOI: 10.1183/09031936.00055107
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen A  Thr312Ala polymorphism is associated with chronic thromboembolic pulmonary hypertension

Abstract: Although chronic thromboembolic pulmonary hypertension (CTEPH) is characterised by the persistence of organised thrombus, few pro-thrombotic risk factors have been identified in subjects with the disease. The aim of the present study was to compare the prevalence of eight functionally relevant haemostatic polymorphisms between CTEPH subjects and healthy controls.Genomic DNA was isolated from 214 CTEPH subjects and 200 healthy controls, and analysed for Factor V Leiden, prothrombin guanine (G) to adenine (A) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 45 publications
5
42
0
2
Order By: Relevance
“…In most cases it is associated with a history of acute venous thromboembolism [19], but why thrombi do not resolve after an acute event in a low percentage of patients is unclear. The current knowledge is based on a triad of enhanced thrombosis [12,20], disturbed thrombolysis [21][22][23] and inflammation [3]. These mechanisms were all investigated in the current experiments regarding CRP effects.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases it is associated with a history of acute venous thromboembolism [19], but why thrombi do not resolve after an acute event in a low percentage of patients is unclear. The current knowledge is based on a triad of enhanced thrombosis [12,20], disturbed thrombolysis [21][22][23] and inflammation [3]. These mechanisms were all investigated in the current experiments regarding CRP effects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a significant difference was demonstrated in fibrinogen (Fg)-Aa Thr312Ala genotype and allele frequencies between CTEPH subjects and controls [52]. In addition, the Fg-Aa Thr312Ala allele has been associated with an increased risk of VTE [53].…”
Section: The Concept Of ''Deficient Angiogenesis''mentioning
confidence: 99%
“…These include a significant association between CTEPH and the fibrinogen Aα polymorphism Thr312Ala, which has been shown to increase the resistance of fibrin to typical lytic processes [53,54]. Taken together, these observations demonstrate a number of pathophysiological modalities that between them probably account for the non-resolution of thromboembolic material seen in CTEPH, although further investigation is required.…”
Section: Coagulation and Thrombus Resolutionmentioning
confidence: 77%